2016
DOI: 10.5604/17307503.1222838
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Neuroticism, Psychoticism and Depression With Visual Evoked Potentials

Abstract: SUMMARYThe aim of this study was to investigate the relationship between visual evoked potentials (N1, P2, N2, P3 and Sw) and levels of neuroticism, psychoticism and depression. Based on previous research, longer EP-latencies were expected in more depressed subjects, and smaller EP-amplitudes in subjects with higher levels of neuroticism and psychoticism. The sample consisted of female psychology students (N=54), age 19-23, all right-handed. After measuring Eysenck's personality dimensions with EPQ/R, and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In the first trial of the study, the first major negative peak between 80 and 100 ms for the rare stimuli was identified as the N100 response. 37 From both trials, the study reported that the most stable relation identified was between P200 amplitude and neuroticism. 37 Furthermore, Chernyshev et al 38 identified that object-related emotionality was positively correlated with P2 and N1-P2 complex amplitudes.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the first trial of the study, the first major negative peak between 80 and 100 ms for the rare stimuli was identified as the N100 response. 37 From both trials, the study reported that the most stable relation identified was between P200 amplitude and neuroticism. 37 Furthermore, Chernyshev et al 38 identified that object-related emotionality was positively correlated with P2 and N1-P2 complex amplitudes.…”
Section: Introductionmentioning
confidence: 96%
“…37 From both trials, the study reported that the most stable relation identified was between P200 amplitude and neuroticism. 37 Furthermore, Chernyshev et al 38 identified that object-related emotionality was positively correlated with P2 and N1-P2 complex amplitudes. On the other hand, both extraversion assessed using the Eysenck personality inventory (EPI) and mobility of nervous process assessed using the Strelau temperament inventory (STI) were negatively correlated with the amplitude of the N1-P2 complex, respectively.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation